Halogen-bond-driven supramolecular assemblies of quaternary-ammonium-iodide-containing polymers in three phases - Le, Hong Tho (2021)
Halogen bonding (XB) opens avenues to supramolecular assemblies. Here, we report XB-driven supramolecular assemblies of quaternary ammonium iodide (QAI)-containing polymers in three (solution, surface, and solid) phases. In the solution, QAI-containing block copolymers form unique self-assembly structures such as micrometer-sized giant vesicles (up to 5-μm diameter) and a 1-dimensional (1D) structure with multiple inter-vesicular linkages via XB. Exploiting the temperature dependence of XB strength, external molecules are successfully loaded and unloaded. On the surface, reversible XB crosslinking and decrosslinking of QAI-containing polymer brushes are achieved. The wettability of the polymer brush is finely tuned by the XB crosslinking density. In solid phase, QAI-containing monomers are co-crystalized (assembled) via XB. A polymer sheet is obtained via the solid-phase polymerization of the monomer co-crystal; the sheet enables capture and release of halogen-containing (XB-coordinating) guest molecules and thereby serves as an innovative host material.